Favorable Mixing Thermodynamics in Ternary Polymer Blends for Realizing High Efficiency Plastic Solar Cells. Issue 19 (1st April 2019) - Gasparini, Nicola; Kahmann, Simon; Salvador, Michael; Perea, Jose Dario; Sperlich, Andreas; Baumann, Andreas; Li, Ning; Rechberger, Stefanie; Spiecker, Erdmann; Dyakonov, Vladimir; Portale, Giuseppe; Loi, Maria A.; et al.
Abstract: Ternary blends with broad spectral absorption have the potential to increase charge generation in organic solar cells but feature additional complexity due to limited intermixing and electronic mismatch. Here, a model system comprising the polymers poly[5, 5‐bis(2‐butyloctyl)‐(2, 2‐bithiophene)‐4, 4‐dicarboxylate‐alt‐5, 5‐2, 2‐bithiophene] (PDCBT) and PTB7‐Th and PC70 BM as an electron accepting unit is presented. The power conversion efficiency (PCE) of the ternary system clearly surpasses the performance of either of the binary systems. The photophysics is governed by a fast energy transfer process from PDCBT to PTB7‐Th, followed by electron transfer at the PTB7‐Th:fullerene interface. The morphological motif in the ternary blend is characterized by polymer fibers. Based on a combination of photophysical analysis, GIWAXS measurements and calculation of the intermolecular parameter, the latter indicating a very favorable molecular affinity between PDCBT and PTB7‐Th, it is proposed that an efficient charge generation mechanism is possible because PTB7‐Th predominantly orients around PDCBT filaments, allowing energy to be effectively relayed from PDCBT to PTB7‐Th. Fullerene can be replaced by a nonfullerene acceptor without sacrifices in charge generation, achieving a PCE above 11%. These results support the idea that thermodynamic mixing and energetics of the polymer–polymer interface are critical design parameter for realizing highly efficient ternary solar cells with variable electron acceptors. Abstract : In this work, organic ternary solar cells based on a model system comprising the polymers PDCBT and PTB7‐Th and PC70 BM are presented as electron accepting units. The photophysics of this blend is governed by a fast energy transfer process from PDCBT to PTB7‐Th allowed by a favorable molecular affinity between PDCBT and PTB7‐Th.